2021
DOI: 10.15605/jafes.036.02.20
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Metformin Use and Mortality Among Patients with Type 2 Diabetes Mellitus Hospitalized for COVID-19 Infection

Abstract: Introduction. Metformin has known mechanistic benefits on COVID-19 infection due to its anti-inflammatory effects and its action on the ACE2 receptor. However, some physicians are reluctant to use it in hypoxemic patients due to potential lactic acidosis. The primary purpose of the study was to determine whether metformin use is associated with survival. We also wanted to determine whether there is a difference in outcomes in subcategories of metformin use, whether at home, in-hospital, or mixed home/in-hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…Ghany et al reported that individuals using metformin at a dose of ≥1000 mg/day had lower mortality than those on 500-850 mg/day [29]. Referenced to nonusers, Ong et al reported the greatest benefit on mortality with the dose from 1000 to <2000 mg/day [52]. Our findings were consistent with these studies.…”
Section: Summary Of Main Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…Ghany et al reported that individuals using metformin at a dose of ≥1000 mg/day had lower mortality than those on 500-850 mg/day [29]. Referenced to nonusers, Ong et al reported the greatest benefit on mortality with the dose from 1000 to <2000 mg/day [52]. Our findings were consistent with these studies.…”
Section: Summary Of Main Findingssupporting
confidence: 89%
“…A total of 3,061,584 participants were recruited from studies . Most of them were retrospective, except for two cross-sectional studies [26,52]. The antidiabetic drugs that were investigated included metformin (42 articles), SU (21), TZD (8), AGI (8), GLP-1RA (12), DPP-4i (28), SGLT-2i (13), and insulin (33) (Table 1).…”
Section: Study and Participant Characteristicsmentioning
confidence: 99%
“…The evidence network comprising 8 glucose-lowering therapies is shown in Figure 2. Among these were 148 active Five studies 25,30,34,37,43 involved more than 7 treatment groups. Eighteen studies had 4 to 6 groups, 23,24,27,28,33,35,36,[39][40][41][44][45][46][47]49,50,52,53 and 5 studies had 3 groups.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Although metformin is associated with an increased risk of developing lactic acidosis during illness, several studies looked at the question of whether or not to continue metformin treatment in patients hospitalized for COVID-19 ( 55 , 66 68 ). One study found that the risk of lactic acidosis associated with metformin exposure was higher in patients with severe COVID-19 disease, patients with kidney impairment, and in patients taking more than 2 doses of metformin daily ( 66 ).…”
Section: Sars-cov-2 and Metforminmentioning
confidence: 99%
“…One study found that the risk of lactic acidosis associated with metformin exposure was higher in patients with severe COVID-19 disease, patients with kidney impairment, and in patients taking more than 2 doses of metformin daily ( 66 ). Interestingly, several studies reported that in-hospital metformin therapy may be beneficial and reduce the risk of mortality in patients hospitalized with COVID-19 ( 55 , 67 , 68 ). It is therefore reasonable to consider continuing metformin therapy during hospitalization if kidney function is carefully monitored; however, further studies are needed before making definitive recommendations.…”
Section: Sars-cov-2 and Metforminmentioning
confidence: 99%